What the Frak, Frankenstein!: Teenagers, Gods, and Postcolonial Monsters on Caprica. Issue 2 (2015) - Thrall, James H.
Abstract : The SyFy television series Caprica (US, 2009-2010), prequel to the series Battlestar Galactica (US, 2004-2009), makes direct and oblique references to Mary Shelley's novel Frankenstein and its film adaptations, including especially James Whale's 1931 Frankenstein . These associations complicate the series' exploration of questions about the nature of life, death, and humanness; help position the created race of Cybernetic Life Form Nodes (Cylons) as simultaneously dangerous and sympathetic; rationalize religious experience in a manner resonant with Shelley's vision of a modern world without God; and support the postcolonial frame the series develops as it considers issues of power, gender, age, ethnicity, and class.